2016
DOI: 10.18632/oncotarget.11427
|View full text |Cite
|
Sign up to set email alerts
|

The ELK3-GATA3 axis orchestrates invasion and metastasis of breast cancer cells in vitro and in vivo

Abstract: Triple-negative breast cancer is a highly aggressive tumor subtype that lacks effective therapeutic targets. Here, we show that ELK3 is overexpressed in a subset of breast cancers, in particular basal-like and normal-like/claudin-low cell lines. Suppression of ELK3 in MDA-MB-231 cells led to transdifferentiation from an invasive mesenchymal phenotype to a non-invasive epithelial phenotype both in vitro and in vivo. Suppression of ELK3 resulted in extensive changes in genome expression profiles. Among these, GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 31 publications
1
53
0
Order By: Relevance
“…ELK3 (also called Net, SAP-2, or ERP) is an ETS domaincontaining transcription factor that forms a ternary complex transcription factor (TCF) together with ELK-1 and serum response factor accessory protein-1 (SAP-1) and binds to a specific DNA sequence through a purine-rich GGA core sequence to regulate the expression of many genes including proto-oncogenes [6,7]. Under basal conditions, ELK3 is a transcriptional repressor, which converts to a transcriptional activator in response to ratsarcoma viral oncogene homolog/ extracellular regulated protein kinases (RAS/ERK) signaling and p38 mitogen-activated protein kinase (MAPK) pathway [8][9][10], and is involved in cell migration, angiogenesis, and malignant progression [11][12][13][14]. Several studies have showed that ELK3 is overexpressed in some cancer cells and correlates with cell migration and invasion [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…ELK3 (also called Net, SAP-2, or ERP) is an ETS domaincontaining transcription factor that forms a ternary complex transcription factor (TCF) together with ELK-1 and serum response factor accessory protein-1 (SAP-1) and binds to a specific DNA sequence through a purine-rich GGA core sequence to regulate the expression of many genes including proto-oncogenes [6,7]. Under basal conditions, ELK3 is a transcriptional repressor, which converts to a transcriptional activator in response to ratsarcoma viral oncogene homolog/ extracellular regulated protein kinases (RAS/ERK) signaling and p38 mitogen-activated protein kinase (MAPK) pathway [8][9][10], and is involved in cell migration, angiogenesis, and malignant progression [11][12][13][14]. Several studies have showed that ELK3 is overexpressed in some cancer cells and correlates with cell migration and invasion [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…ELK3 is constitutively activated in basal triple negative breast cancer cells (TNBCs) and functions as a master regulator of cancer metastasis (10,12). Previously, we suggested that the TGFβ signaling pathway is interconnected with ELK3 activity, based on the fact that ELK3 knockdown in TNBCs induces collapse of TGFβ signaling (12). In this study, we demonstrated that ELK3 is transcriptionally activated by TGFβ treatment in TNBCs.…”
Section: Discussionmentioning
confidence: 62%
“…During cancer development and progression in malignancy, the TGFβ signaling pathway acts as a tumor promotor by driving EMT, which induces tumor cell migration, invasion and ultimately metastasis to distant organs. ELK3 is constitutively activated in basal triple negative breast cancer cells (TNBCs) and functions as a master regulator of cancer metastasis (10,12). Previously, we suggested that the TGFβ signaling pathway is interconnected with ELK3 activity, based on the fact that ELK3 knockdown in TNBCs induces collapse of TGFβ signaling (12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations